2017
DOI: 10.1128/aac.01627-16
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of CD101 IV, a Novel Echinocandin, in Healthy Adults

Abstract: CD101 IV is a novel echinocandin with distinctive pharmacokinetic properties that is being developed as a once-weekly treatment for candidemia and invasive candidiasis. CD101 has potent in vitro activity and in vivo efficacy against a broad range of Candida and Aspergillus species. The primary objective of two randomized, double-blind, placebo-controlled, dose-escalation studies in healthy adults was to determine the safety and tolerability of CD101 IV. Sequential cohorts of 8 subjects (n = 6, active; n = 2, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 35 publications
4
102
0
2
Order By: Relevance
“…However, comparisons of previous ex vivo studies using the same methods to in vivo CRRT trials of the same drug [16, 17] have shown good agreement in clearance estimates. Our findings of an SC not different from zero in the ex vivo model are very consistent with what is known about the extensive (97–99%) protein binding in humans receiving rezafungin [10]. …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, comparisons of previous ex vivo studies using the same methods to in vivo CRRT trials of the same drug [16, 17] have shown good agreement in clearance estimates. Our findings of an SC not different from zero in the ex vivo model are very consistent with what is known about the extensive (97–99%) protein binding in humans receiving rezafungin [10]. …”
Section: Discussionsupporting
confidence: 80%
“…The blood was continuously stirred and heated to 37°C in a water bath during all experiments. Reconstituted rezafungin (Lot number AMU252277; Cidara Therapeutics, San Diego, CA, USA) was added to blood to achieve the final concentration of ~30 mg/L (approximating the plasma peak concentration following multiple once-weekly 400 mg doses [10]). Urea (Lot number 30K0221; Sigma, St. Louis, MO, USA) was used as a control and added to the blood to produce a blood urea nitrogen concentration of ~75 mg/dL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of CD101 in human is about 3-fold longer (about 90 h) than that of anidulafungin (about 30 h) (10). It should be noted that 90 h is the effective half-life of CD101 (i.e., the half-life that covers the majority of the AUC), with a longer, later-phase half-life evident at lower concentrations beyond the first week after dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike currently approved once-daily, IV-only echinocandins, CD101 is highly stable, enabling additional formulations and potential uses. In preclinical and phase 1 studies conducted to date, CD101 has demonstrated distinctive PK characteristics, notably the ability to safely achieve high plasma concentrations and an exceptionally long half-life ( t 1/2 ) (9, 10). …”
Section: Introductionmentioning
confidence: 99%